Attitudes of Chinese College Students Toward Aging and Living Independently in the Context of China’s Modernization: A Qualitative Study - Zhang, Yan; Wang, Junxiu; Zu, Yanfei; Hu, Qian (Frontiers in Psychology, 2021)
Modernization in China is accompanied by some specific features: aging, individualization, the emergence of the nuclear family, and changing filial piety. While young Chinese people are still the main caregivers for older adults, understanding the attitudes of young Chinese people toward aging and living independently in the context of modernization is important because it relates to future elderly care problems in China. By using in-depth interviews and qualitative methods, 45 participants were enrolled in the study, 38 (84.44%) were women and 37 (82.22%) had no siblings. The ages ranged from 17 to 23 years (mean age = 19.24, SD = 1.61). Results revealed that participants held diverse attitudes about older adults, but the general attitudes were that older adults are lonely, financially disadvantaged, have poor social support, lack hobbies, and care about their children more than themselves. Chinese college students seemed affected both by traditional filial piety and individualism; however, of the two, they put greater value on independence. Moreover, traditional filial piety is changing in a modern direction, affected by Western ideas of individualism: the status of the senior is diminishing and living with one’s parents is no longer regarded as a necessary component. Implications concerning age stereotypes, elderly care policies, and strategies were discussed.